Development of SageMath filter for Moodle - E. O. Modlo; S. O. Semerikov (Academy of Cognitive and Natural Sciences, 2014)
Research goals: determine the characteristics of the development process, installation, configuration and usage of the filter SageMath for learning support system Moodle. Research objectives: to prove the feasibility of using Moodle system as a tool to support the process of competency formation in technical objects simulation of future bachelors in electromechanical engineering; to analyze existing support tools of technical objects simulation and to identify the ways of it's integration into Moodle; to describe the structure and features of the software implementation of the new SageMath filter for Moodle; to provide the guidance on installing and configuring developed filter; to describe the examples of filter usage. Research object: computer mathematics and learning support systems integration. Research subject: text filter development process for learning support system Moodle to processing the commands of computer mathematics system SageMath. Research methods used: analysis of state educational standards and existing application, software engineering process. Research results. Designed SageMath filter allows to execute the Sage code on the external SageMathCell public server, to view the execution results at the Moodle pages without reloading by using AJAX technology, to stave off XSS attacks and ready for use with Moodle. The main conclusions and recommendations: 1. The perspective direction of learning environment development for bachelors in electromechanical engineering is the integration of learning support system Moodle and computer mathematics system SageMath. 2. An effective tool for embedded a computer mathematics systems SageMath models into Moodle is a text filter. The software engineering process for this filter is presented in the article. 3. Promising area of future research is the use of a developed filter in the process of bachelor's in electromechanical engineering competencies in technical objects simulation by embedding into Moodle learning courses the interactive labs programmed in Sage.